Penerapan Algoritma Support Vector Machine Pada Review Aplikasi Tiktok - Irdianto, Nahdah Arlisa; Putri, Raissa Amanda (STMIK Banjarbaru, 2024)
This research aims to evaluate the application of the Support Vector Machine (SVM) algorithm in classifying user reviews of the TikTok application. The research process consists of three main stages, namely: data crawling to collect user reviews, data preprocessing to clean and prepare the data, and a classification process using the SVM algorithm. In the crawling stage, TikTok user reviews are collected from various sources. Then, in the preprocessing stage, the raw data is cleaned from irrelevant elements and converted into a format that can be processed by the SVM algorithm. Finally, in the classification stage, the SVM algorithm is applied to classify the reviews. The research results show that from a total of 399 test data, the SVM algorithm succeeded in classifying 299 data correctly, resulting in an accuracy rate of 75%. This shows that the SVM algorithm has good capabilities in classifying user reviews of the TikTok application, although there is still room for improvement. This research contributes to the understanding of the application of SVM algorithms for sentiment analysis and text classification in the context of social media application reviews.Keywords: Support vector machine; Classification; TikTok; Sentiment analysisÂ Â AbstrakPenelitian ini bertujuan untuk mengevaluasi penerapan algoritma Support Vector Machine (SVM) dalam klasifikasi ulasan pengguna aplikasi TikTok. Proses penelitian terdiri dari tiga tahap utama, yaitu: crawling data untuk mengumpulkan ulasan pengguna, preprocessing data untuk membersihkan dan mempersiapkan data, serta proses klasifikasi menggunakan algoritma SVM. Pada tahap crawling, ulasan pengguna TikTok dikumpulkan dari berbagai sumber. Kemudian, pada tahap preprocessing, data mentah dibersihkan dari elemen-elemen yang tidak relevan dan diubah menjadi format yang dapat diproses oleh algoritma SVM. Terakhir, pada tahap klasifikasi, algoritma SVM diterapkan untuk mengklasifikasikan ulasan-ulasan tersebut. Hasil penelitian menunjukkan bahwa dari total 399 data uji, algoritma SVM berhasil mengklasifikasikan 299 data dengan benar, menghasilkan tingkat akurasi sebesar 75%. Hal ini menunjukkan bahwa algoritma SVM memiliki kemampuan yang baik dalam melakukan klasifikasi ulasan pengguna aplikasi TikTok, meskipun masih terdapat ruang untuk perbaikan. Penelitian ini memberikan kontribusi dalam pemahaman tentang penerapan algoritma SVM untuk analisis sentimen dan klasifikasi teks dalam konteks ulasan aplikasi media sosial.Kata kunci: Support vector machine; Klasifikasi; TikTok; Analisis sentimen